The Importance of Normal Microflora in the Occurrence and Course of Diseases - Rustamdzhanovna, Nargiza Rakhimova (American Journal of Bioscience and Clinical Integrity, 2024)
Since its discovery, many studies have been conducted on the role of microbiota in health and disease. Microbiota are divided into intestinal, oral, respiratory and skin microbiota depending on where they are located. Microbial communities interact with the host to maintain homeostasis and regulate the immune system. However, microbiota dysbiosis can disrupt the regulation of body functions and diseases such as cancer, respiratory diseases, cardiovascular diseases, etc. In this review, we discuss current knowledge about how the microbiota is related to host health or its pathogenesis. First, we summarize microbiota studies in healthy settings, including immune modulation, the gut-brain axis, and resistance to colonization. Then we consider the causes of microbiota dysbiosis in the development and spread of diseases. First of all, we consider the problems associated with a change in the composition of the community, a change in the host’s immune response and the occurrence of prolonged inflammation. Finally, we propose clinical treatments for diseases using microbiota, such as microbiota modulation and fecal microbial transplantation.